2010
DOI: 10.1016/j.jmb.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Core Regions of Human Lysozyme Amyloid Fibrils Influence Cytotoxicity

Abstract: Identifying the cause of the cytotoxicity of species populated during amyloid formation is crucial to understand the molecular basis of protein deposition diseases. We have examined different types of aggregates formed by lysozyme, a protein found as fibrillar deposits in patients with familial systemic amyloidosis, by infrared spectroscopy, transmission electron microscopy, and depolymerization experiments, and analyzed how they affect cell viability. We have characterized two types of human lysozyme amyloid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
94
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 56 publications
13
94
0
Order By: Relevance
“…Toxicity can be due to the exposure of normally buried moieties such as hydrophobic side chains or free main chain NH and CO groups that can lead to non-native hydrogen bond interactions with other proteins (Mossuto et al, 2010). Indeed, several studies have shown that sequestration of metastable and essential cellular factors such as proteins involved in chromatin remodeling, transcription, translation, nuclear import and cytoskeletal structure by the aggregates is the major cause of observed toxicity in vivo (Bucciantini et al, 2002;Chai et al, 2002;Olzscha et al, 2011;Suhr et al, 2001).…”
Section: Prion Protein Extracellularmentioning
confidence: 99%
“…Toxicity can be due to the exposure of normally buried moieties such as hydrophobic side chains or free main chain NH and CO groups that can lead to non-native hydrogen bond interactions with other proteins (Mossuto et al, 2010). Indeed, several studies have shown that sequestration of metastable and essential cellular factors such as proteins involved in chromatin remodeling, transcription, translation, nuclear import and cytoskeletal structure by the aggregates is the major cause of observed toxicity in vivo (Bucciantini et al, 2002;Chai et al, 2002;Olzscha et al, 2011;Suhr et al, 2001).…”
Section: Prion Protein Extracellularmentioning
confidence: 99%
“…found to be cytotoxic [3][4][5][6] or to induce the dysfunction of neurons and neuronal loss [7]. The binding of anle138b might inhibit aggregate growth and/or could reduce the toxicity of the aggregates and hamper disease progression as observed in in vivo experiments [16].…”
Section: Tablementioning
confidence: 99%
“…These aggregates, located in the brain of infected individuals, are characterized by a cross-β-sheet protein structure and a fibrillar morphology under the electron microscope. The amyloid aggregates are considered to play an important role in the pathogenesis of neurodegenerative diseases [3][4][5][6][7]. Furthermore, recent experiments pointed out that not only the fibrillar structures but especially the formation of smaller, highly cytotoxic oligomeric forms [8] might lead to neuronal loss [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In the final steady state or stationary phase, fibrils and monomers are in equilibrium and the structure of the fibrils can still evolve for example by rearrangement of the region of the protein that is not part of the core of the fibrils, leading to mature fibrils [11]. Besides, the amyloid fibrils can also associate laterally [12]. The lag phase can be shortened or even suppressed by the addition of seeds (i.e.…”
Section: Introductionmentioning
confidence: 99%